Бюджетний менеджмент у системі забезпечення фінансової безпеки країни в умовах економічних трансформацій - Яцух, Олена Олексіївна; Yatsukh, Olena (My University, 2026)
UA: Метою статті є дослідження теоретичних і прикладних засад бюджетного менеджменту у системі забезпечення фінансової безпеки держави в умовах економічних трансформацій, а також визначення ключових напрямів підвищення ефективності формування доходної бази бюджету та удосконалення механізмів управління публічними фінансами. У процесі дослідження використано комплекс загальнонаукових і спеціальних методів, зокрема методи системного та інституційного аналізу, узагальнення та порівняння, статистичний і економіко-аналітичний методи, що дало змогу дослідити тенденції формування доходів державного бюджету України, оцінити структуру податкових надходжень та визначити ключові фактори забезпечення фінансової безпеки держави. Інформаційною базою дослідження стали статистичні дані щодо доходів державного бюджету, податкових надходжень і макрофінансових показників розвитку системи публічних фінансів. /// EN: The purpose of the article is to study the theoretical and methodological foundations of managing budgetary stability and state financial security under conditions of economic transformations. The research focuses on identifying key factors influencing the sustainability of the public finance system and determining strategic directions for improving the efficiency of budget policy and public financial management. The study applies a combination of general scientific and special research methods, including systemic analysis, comparative analysis, synthesis and generalization, as well as statistical and economic analysis. These methods made it possible to evaluate the dynamics of public budget revenues, analyze the structure of tax revenues, and identify macroeconomic indicators that determine the level of budgetary stability and financial security of the state. The empirical basis of the study includes official statistical data on public finance indicators and budget revenues. The article clarifies the conceptual content of budgetary stability and state financial security as interrelated elements of the public finance system. It is substantiated that effective budget management requires a balanced combination of fiscal policy instruments, tax administration mechanisms and debt management tools. The analysis of the dynamics of state budget revenues demonstrates a steady increase in financial resources over the studied period, which is largely determined by the growth of tax revenues and the involvement of international financial assistance.
Budget management in the system of ensuring state financial security under conditions of economic transformations
Keywords: бюджетний менеджмент; фінансова безпека держави; податкові надходження; бюджетна політика; публічні фінанси; стратегічне управління; budget management; state financial security; public finance management; tax revenues; fiscal policy; digitalization of public finance